Pembangunan Pembangkit Listrik Tenga Surya untuk Petani Sayur di Desa Kualu Nenas Kabupaten Kampar - Iswadi Hasyim Rosma; Feblil Huda; Agus Ika Putra; Arisman Adnan; Ahmad Jamaan (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
This article aims to describe community service activities carried out by the implementation team in Kualu Nenas village, Tambang District, Kampar Regency, Riau. As a village and sub-district that is very close to the city of Pekanbaru which is the capital of Riau province, this village has a very important role as a supplier of vegetable commodities. One of the difficulty faced by farmer groups is that during dry season (sunny), water sources, as one of the important factors in vegetable crops, are very difficult to obtain. To overcome this, this community engagement aims to build the solar photovoltaic generation system as an energy source for submersible pump motors to draw water from the location of water sources and deep well made by farmers on their land. With this solar PV generation system, agricultural locations that are remote from national grid (PT PLN) supply can still operate their pump motors to get water. The stages of this activity are divided into several stages, including surveying the solar PV system construction site, designing solar PV generation system and building solar PV generation system so that it can be operated properly. This activity could run well with the support and cooperation of farmer partners who are actively involved in every stage conducted.